Characterization of metals in feed, litter and air of intensive poultry farming facilities - Yasmeen, Roheela; Hafeez, Faheem; Ammara, Umme; Younas, Rubab; Ahmad, Sibtain; Ali, Zulfiqar; Nasir, Zaheer A. (Researchers Links, 2023)
Poultry industry is progressing worldwide due to cheap sources of proteins and it is also considered as the center of various organic and inorganic emissions. The current study was designed to see the release of different metals from the poultry farms. Air samples both from indoor and outdoor along with the litter and feed samples of ten poultry houses were collected from the outskirts of Lahore, Punjab, Pakistan. Poultry farms were varied in feed and grouped into three categories: Group A (using Feed A), Group B (using Feed B) and Group C (using Feed C). All collected samples were digested with aqua regia and analyzed by Inductively Coupled Plasma Atomic Mass Spectroscopy (ICP-MS). Fourteen metals were detected and categorized as essential (Calcium (Ca), Potassium (K), Sodium (Na), Phosphorus (P), Magnesium (Mg)), trace (Zinc (Zn), Copper (Cu), Iron (Fe), Manganese (Mn)) and heavy metals (Cadmium (Cd), Chromium (Cr), Mercury (Hg), Nickel (Ni), Lead (Pb)). In general, the concentration of all essential, trace, and heavy metals was found to be highest in feed followed by litter and air samples. However, Cr, Hg and Pb were higher in litter samples of group A as compared to feed and air. All the samples were statistically analyzed using one way ANOVA. A significant difference of feed was present with litter and air samples within groups (p<0.05) however, no significant differences were recorded among different groups. Overall it was noticed that the concentration of metals in feed samples were reflecting in litter and air. So, there is a need to ensure intervention and management policies in intensive poultry farming facilities to establish standards for metal in feed to reduce their bioaccumulation in the environment.
Keywords: Feed; Indoor air; Litter; Metals; Outdoor air